Individual Counseling Client-Centered Approach in Increasing the Resilience of Victims of Bullying - Fitri, Hartika Utami; Rasmanah, Manah; Kushendar, Kushendar; Hernisawati, Hernisawati (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
Resilience is an aspect that is owned by individuals in dealing with pressure or challenges. Individuals in health need Resilience. The hectic bullying among teenagers is a phenomenon that has not been fully resolved. This study aims to determine the effectiveness of individual counseling with the client-centred approach in increasing victim resilience-bullying. The methodology in this research is a quantitative experiment, design pre-experiment type and Post-experiment. The sampling technique in this study uses purposive sampling. The sample in this study was two respondents data analysis using Single Subject Research (SSR) with A design1-B-A2. The research results show that the resilience of bullying victims is classified as low with a score for respondent